2000
DOI: 10.1590/1809-43922000301166
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição sazonal das larvas de Mylossoma aureum e Μ. duriventre (osteichthyes: serrasalmidae) na Costa do Catalão, Rio Amazonas, Amazonas, Brasil

Abstract: RESUMO -A distribuição sazonal das larvas de Mylossoma aureum e M. duriventre (Osteichthyes: Serrasalmidae), foi estudada na costa do Catalão, rio Amazonas durante três anos. As larvas de ambas espécies de Mylossoma foram mais abundantes na estação marginal do que na estação localizada no centro do rio. O período de ocorrência das duas espécies foi semelhante e durou em média 109 dias, variando de novembro-janeiro a abril-maio. A variação na abundância de larvas durante o período de ocorrência não se relaciono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
3
2
0
2
Order By: Relevance
“…The high densities of larvae in areas at the mouths of lake channels and barrancos are consistent with the results of Oliveira and Araújo‐Lima () and Oliveira (). These authors also found a higher quantity of Characiformes larvae by the shores, and a lower density in the central channel of the Amazon River.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The high densities of larvae in areas at the mouths of lake channels and barrancos are consistent with the results of Oliveira and Araújo‐Lima () and Oliveira (). These authors also found a higher quantity of Characiformes larvae by the shores, and a lower density in the central channel of the Amazon River.…”
Section: Discussionsupporting
confidence: 91%
“…Such temporal patterns need to be understood to provide reliable evaluation of fish status and accurate basis for planning, and ensure healthy, well‐managed fisheries (Booth, ; Shuai et al., ). However, in the Amazon, studies of ecology and distribution the fish larvae remain scarce; exceptions are the studies of Oliveira and Araújo‐Lima (), Oliveira (), Araújo‐Lima, Silva, Petry, Oliveira and Moura (), Lima and Araújo‐Lima (), Oliveira and Ferreira (), Mounic‐Silva and Leite (), Ponte et al. (), Zacardi and Ponte () and Chaves et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…were more abundant in the ravines, which are areas of erosion, similar to that described for the fish larvae of the Missouri River in microhabitats with these characteristics (Hergenrader et al, 1982), and for Mylossoma aureum and M. duriventre in the margins of the Amazon River Oliveira, 2000). This pattern probably gives advantages to the species of Plagioscion that would be more easily transported to the nursery areas, such as lake channels and lakes.…”
Section: Microhabitat Distribution Of Larvaesupporting
confidence: 73%
“…Na Amazônia, todos os trabalhos realizados sobre distribuição de ovos e larvas de Characiformes foram desenvolvidos nos rios Solimões e Amazonas (Araújo-Lima, 1984;Petry, 1989;Oliveira, 1996;Araújo-Lima & Oliveira. 1998;Oliveira & Araújo-Lima, 1998;Oliveira, 2000) que são rios de águas brancas.…”
unclassified